Prediction of hypertension in pregnancy in high risk women using maternal factors and serial placental profile in second and third trimester. (15th January 2021) - Hasija, Aayushi; Balyan, Kirti; Debnath, Ekta; V, Ravi; Kumar, Manisha
Abstract: Introduction: To evaluate the role of placental profile markers in second and third trimester of pregnancy in predicting hypertensive disorders of pregnancy (HDP) in women at high risk of preeclampsia. Method: Women who were at high risk of preeclampsia underwent βhCG, ultrasound assessment of placental length, thickness and its ratio, uterine artery Doppler at 20–24 weeks and 28–32 weeks of gestation, the outcome at delivery was noted. Those who developed HDP were cases and those with normal outcome were controls. The placental profile markers among cases and controls were compared. Results: Hypertensive disorders of pregnancy was seen in 72/160 (45%) high risk women The serum β hCG levels at 20–24 weeks (p = 0.001) and 28–32 weeks (p = 0.018) was significantly high in women who had preeclampsia. Placental thickness was found to be less in among all subgroups of HDP, for preeclampsia, it was significantly low at 20–24 weeks (AUC- 0.743; sensitivity- 75%, specificity- 66.3%) and 28 weeks (AUC -0.764, sensitivity - 75.0% specificity - 78.7%). Uterine artery S/D ratio was considerable high in women with chronic hypertension (AUC -0.765), gestational hypertension (AUC -0.771) and preeclampsia (AUC -0.726) at 20–24 weeks. In preeclampsia group, uterine artery PI was highest and the best marker at 20–24 weeks (AUC -0.935, sensitivity - 100.0%, specificity - 87.6%). Discussion: The placental profile markers may be used to provide closer follow up in high risk pregnancies with abnormal placental profile levels, while less intense follow up in those with normal levels, thus channelizing the resources. Highlights: Abnormal placentation is the initial event in causing pregnancy hypertension. Decreased placental thickness is associated with hypertension in pregnancy (HDP). Uterine Doppler PI & S/D ratio were the important markers for prediction of HDP. Screening of high-risk women would aid in their risk stratification.